High performance broadband photo and soft X-ray detectors based on two dimensional CrSiTe3. Issue 20 (18th May 2020) - Li, Yun; Liu, Jingying; Su, Xin; Ou, Qingdong; Wan, Zhichen; Wu, Yingjie; Yu, Wenzhi; Bao, Xiaozhi; Huang, Yamin; Wang, Xiaomu; Tadich, Anton; Shabbir, Babar; et al.
Abstract : Here we demonstrate a room temperature, high performance broadband photodetector based on van der Waals magnetic material CrSiTe3 that can efficiently detect both soft X-rays and light in the near-infrared (NIR) and visible wavelength ranges. Abstract : Broadband photodetectors are essential for various applications including spectroscopy, communication, imaging and sensing. Even though few materials show broadband photodetection, they are only capable of detecting light in limited spectral ranges from infrared (IR) to ultraviolet (UV) wavelengths. However, their functionalities at much shorter wavelengths such as ionizing radiation still present a challenge because of the limitations from the material properties. Here we demonstrate a room temperature, high performance broadband photodetector based on van der Waals (vdWs) magnetic material CrSiTe3 (CST) that can efficiently detect both soft X-rays and light in the near-infrared (NIR) and visible wavelength ranges. The CrSiTe3 based device can work with a high sensitivity (≈463 μC Gyair −1 cm −2 ) under synchrotron soft X-rays, which is more than twenty times more sensitive than the conventional α-Se device. In the NIR range, the device can achieve a maximum responsivity of around 206 A W −1 at 785 nm, an extremely high external quantum efficiency (EQE) of 32 600%, a detectivity of 1.25 × 10 12 cm Hz 1/2 W −1 and a relatively fast photoresponse time (rise time ∼43 ms under X-rays, 17 ms under a 785 nm laser). Together these results demonstrate a high-performance broadband photo and X-ray detector, offering intriguing opportunities for novel optoelectronic applications.